Metabolic flexibility to lipid availability during exercise is enhanced in individuals with high insulin sensitivity - Fernández-Verdejo, Rodrigo (Am J Physiol Endocrinol Metab, 2018)
Metabolic flexibility to lipid (MetFlex-lip) is the capacity to adapt lipid oxidation to lipid availability. Hypothetically, impaired MetFlex-lip in skeletal muscle induces accumulation of lipid metabolites that interfere with insulin signaling. Our aim was to compare MetFlex-lip during exercise in subjects with low (Low_IS) vs. high (High_IS) insulin sensitivity. Twenty healthy men were designated as Low_IS or High_IS on the basis of the median of the homeostatic model assessment of insulin resistance index. Groups had similar age, body mass index, and maximum oxygen uptake (V̇o(2max)). Subjects cycled at 50% V̇o(2max) until expending 650 kcal. Adaptation in lipid oxidation was calculated as the drop in respiratory quotient (RQ) at the end of exercise vs. the maximum RQ (ΔRQ). Lipid availability was calculated as the increase in circulating nonesterified fatty acids (NEFA) at the end of exercise vs. the minimum NEFA (ΔNEFA). ΔRQ as a function of ΔNEFA was used to determine MetFlex-lip. On average, RQ and circulating NEFA changed similarly in both groups. However, ΔRQ correlated with ΔNEFA in High_IS (r = −0.83, P < 0.01) but not in Low_IS (r = −0.25, P = 0.48) subjects. Thus the slope of the ΔRQ vs. ΔNEFA relationship was steeper in High_IS vs. Low_IS subjects (−0.139 ± 0.03 vs. −0.025 ± 0.03 RQ·mmol(−1)·l(−1), respectively; P < 0.05), with similar intercepts. We conclude that in subjects with High_IS lipid-to-carbohydrate oxidation ratio adapts to the increased circulating NEFA availability during exercise. Such MetFlex-lip appears impaired in subjects with Low_IS. Whether a cause-effect relationship exists between impaired MetFlex-lip and low insulin sensitivity remains to be determined.